Effect of ultrasonic reactor and auxiliary stirring on oil removal from oily sludge. Issue 24 (17th December 2017) - Zhao, Xiaofei; Zhang, Xiaoyang; Liu, Lixin; Fan, Lei; Ge, Dan
ABSTRACT: In this paper, oily sludge cleaning by using ultrasonic waves was further studied to ensure how the ultrasonic reactor, such as material, bottom thickness, diameter, and auxiliary mixing, effects oil removal from oily sludge. Oily sludge (S) with an initial oil content of 19.29% was mixed with distilled water (W) and treated in an ultrasonic cleaning tank, f = 40, 000 Hz at 30°C. This paper was carried out around the ultrasonic reactor, such as material, diameter, and bottom thickness. The results show that acoustic resistance is the main factor affecting the material of the ultrasonic reactor. The larger the diameter of the reaction, the lower the thickness of the S-W mixture of the same quality; the smaller the diffusion attenuation of the ultrasonic wave, the higher the oil removal rate. In this paper, the cleaning efficiency seems to be independent of the bottom thickness of the reactor. This may be due to the hale wavelengths ( λ /2) in polyethylene ( λ /2 = 2.4 cm) and glass ( λ /2 = 7.08 cm) being far greater than the range of bottom thickness. Proper mixing (200 rmin −1 ) can improve the oil removal rate (92.8%), increased by 8.69%, but when the strength is too large, the oil removal rate is reduced.